Narratives of the convalescent plasma donor in a Peruvian social security hospital.: motivations, fears, expectations and experiences. - Matassini Eyzaguirre, Silvana M. (2023)
Objectives: To know and explore from convalescent plasma donators' voices the experience in the blood donation process at a social security hospital. Material and Methods: Qualitative study with a phenomenological design. The investigation was carried out in 01 hospitals of the social security of Peru. Semi-structured interviews were carried out. Results: Eleven donors of convalescent plasma were interviewed. The main motivations for donating were being able to contribute to national research and supporting patients affected by COVID-19. Fears focus on the possible risk of contagion within the hospital. Donors emphasised the attention and support of health personnel alongside the donation procedure. The main expectations and suggestions point towards greater dissemination of donation campaigns with special emphasis on safety. Likewise, an improvement in the time of the donation procedure (from enrolment to the extraction of convalescent plasma), and the implementation of friendly spaces to encourage future blood donation campaigns were highlighted. Conclusions: The experience of the convalescent plasma donors was positive. However, improvements must be made in terms of processes and infrastructure to ensure future successful blood donation campaigns.